The Use of Public-Private Partnerships as a Model for the Delivery of Goods and Services to the Government - Is This a New Concept in Government Contracting? - Napoleon, Vincent J.; Vilmenay, Diana V.; Newton, Nia (Journal of Law and Commerce, 2017)
N/A